An Analysis of Gender Based Participation In the Context of Participatory Development Approaches: The Case of Community Development Projects in Kongwa District, Dodoma, Tanzania - Mhando, D. G.; Nindi, S. J.; Ganja, S. K. (Tanzania Journal for Population studies and Development, 2009)
Bottom-up development approach has fostered greater emphasis on the current popularly accepted participatory methodologies as an important development strategy tool. Institutionalisation of participatory rural appraisal and, opportunities and obstacle to development methodology underscore the importance of participatory approaches. This paper analysed gender participation basing on the conflicting interests and differences in some of the projects executed through participatory development approaches. The study randomly interviewed a sample of 100 respondents from two villages. It used questionnaires, checklist and Harvard analytical framework for data collection. Results showed that about 53% of the respondents did not understand the meaning of participation and participatory approach; and women laboured most in community development projects. Socio-cultural, participatory tool application, economic, and nature of the project were the factors found to influence major variation in gender participation. The paper recommends that participatory methodology and gender analytical framework be formalised by PRA activists to facilitate local leaders and the entire community in defining gender attribute, socio-cultural and economic differences prior to project execution. Planners should ensure that capacities and capacitating strategies, in terms of skills and resources to participatory development practitioner, are given priority. Also, policies should stipulate gender analytical components as a must criterion for project approval.